The ‘Vandal’ epigram - Magnus Snaedal (Filologia Germanica, 2025)
The paper deals with a Latin epigram, Inter eils goticum etc., often referred to as the ‘Gothic’ epigram. It contains some Germanic words that have generally been considered to be Gothic but here the view is taken that they are of a Vandal origin. In the first section of the paper the manuscript tradition of the epigram, its origin and editions are overviewed. In the second section the interpretations, so far, of the Germanic words are discussed and a new interpretation is proposed. Then the metre and the possible occasion of the epigram are also dealt with. At the end the main conclusions are summarized.